2003
DOI: 10.1046/j.1439-0450.2003.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Tank Milk Analysis: Factors Associated with Appearance ofMycoplasmasp. in Milk

Abstract: Factors associated with the presence of Mycoplasma sp. in bulk tank milk samples were evaluated from 664 herds during 2.25 years. Milk quality components were not strongly related to the presence of Mycoplasma sp. in bulk tank milk. The presence of other contagious mastitis pathogens, Staphylococcus aureus and Streptococcus agalactiae, was also not related to the presence of mycoplasma, suggesting that the aetiology and transmission of mycoplasma mastitis were different from transmission of other contagious ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 6 publications
9
33
2
7
Order By: Relevance
“…Several studies report that the presence of other contagious mastitis pathogens, as S. aureus, is not affected to the presence of mycoplasma, suggesting that the aetiology and transmission of mycoplasma mastitis are different from transmission of other contagious mastitis pathogens (de la Fe et al, 2009;Fox et al, 2003). Our data, here, shows that infection with these two microorganism leads to an increased impact on milk production due.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Several studies report that the presence of other contagious mastitis pathogens, as S. aureus, is not affected to the presence of mycoplasma, suggesting that the aetiology and transmission of mycoplasma mastitis are different from transmission of other contagious mastitis pathogens (de la Fe et al, 2009;Fox et al, 2003). Our data, here, shows that infection with these two microorganism leads to an increased impact on milk production due.…”
Section: Resultssupporting
confidence: 50%
“…Discordant data about the effects of CA on milk composition are present in the literature: some authors reported significant effects (Burriel, 1997;Leitner et al, 2003) while other authors do not (de la Fe et al, 2009;Fox et al, 2003). The effect of mycoplasma infection on milk protein and casein percentages is probably due to reduced udder functionality, that leads to lower synthesis of casein and protein milk.…”
Section: Resultsmentioning
confidence: 96%
“…28 Herd replacement cattle exposed to cattle outside the herd, either imported or reared off-site, increased with increasing herd size, a biosecurity risk factor. 29 It was found that herd size 10,30 and culling 30 were risk factors for increased herd prevalence of Mycoplasma mastitis. Presumably this is a result of herd expansion, the entrance of new cattle with symptomatic, or asymptomatic carriage of new strains of Mycoplasma sp into the herd.…”
Section: Bovis M Californicum M Bovigenitalium Othermentioning
confidence: 99%
“…First, a potential problem with Mycoplasma mastitis must be known and cows suspected of Mycoplasma mastitis must be identified and verified as diseased. Culture of bulk tank milk on a regular basis is a method to monitor a herd's Mycoplasma mastitis status, 10,16,81 and such regular sampling and culture of bulk tank milk as a monitor of Mycoplasma mastitis in a herd have been advocated. 52 It is generally believed that the culture of Mycoplasma sp from bulk tank milk is indicative of at least one herd cow having Mycoplasma mastitis, although a negative culture does not necessarily indicate that the herd is free of this disease.…”
Section: Controlmentioning
confidence: 99%
“…As contagiosas são as causadas por micro-organismos conhecidos como "vaca dependentes" que tem como reservatório a glândula mamária como Staphylococcus aureus, várias espécies de Staphylococcus coagulase negativa, Streptococcus agalactiae, Corybacterium bovis e Mycoplasma spp. (Fox et al 2003, Langoni 2013, que são transmitidas a partir de vacas infectadas para outras no momento da ordenha pelas mãos dos ordenadores, equipamentos de ordenha e outros fômites de uso comum entre os animais, e as ambientais, que são causadas por micro-organismos, cuja fonte primária é o próprio ambiente onde os animais são mantidos, como camas, sala de ordenha, entre outros, e a transmissão ocorre principalmente após a ordenha. Nesse caso, tem-se as enterobactérias, como Escherichia coli, Klebsiella pneumoniae, Enterobacter spp, Streptococcus uberis e Streptococcus dysgalactiae, Pseudomonas spp.,…”
Section: Introductionunclassified